BRIDGE TO THE FUTURE BETWEEN SCIENCE AND PRODUCTION (FOLLOWING THE RESULTS OF THE 21-TH INTERNATIONAL SCIENTIFIC CONFERENCE «FOUNDRY AND METALLURGY 2013. BELARUS») - Yu. N. Fasevich (Литьë и металлургия, 2013)
.